Evaluation of dual‐energy X‐ray absorptiometry compared to magnetic resonance imaging for collecting measurements of the human bony pelvis. Issue 8 (23rd April 2022) - Decrausaz, Sarah‐Louise; Shirley, Meghan K.; Stock, Jay T.; Williams, Jane E.; Fewtrell, Mary S.; Clark, Chris A.; Arthurs, Owen J.; Wells, Jonathan C. K.
Abstract: Objectives: Imaging methods to measure the human pelvis in vivo provide opportunities to better understand pelvic variation and adaptation. Magnetic resonance imaging (MRI) provides high‐resolution images, but is more expensive than dual‐energy X‐ray absorptiometry (DXA). We sought to compare pelvic breadth measurements collected from the same individuals using both methods, to investigate if there are systematic differences in pelvic measurement between these imaging methods. Methods: Three pelvic breadth dimensions (bi‐iliac breadth, bi‐acetabular breadth, medio‐lateral inlet breadth) were collected from MRI and DXA scans of a cross‐sectional sample of healthy, nulliparous adult women of South Asian ancestry ( n  = 63). Measurements of MRI and DXA pelvic dimensions were collected four times in total, with one baseline data collection session and three replications. Data collected from these sessions were averaged, used to calculate technical error of measurement and entered into a Bland–Altman analysis. Linear regression models were fitted with a given MRI pelvic measurement regressed on the same measurement collected from DXA scans, as well as MRI mean bias regressed on DXA mean bias. Results: Technical error of measurement was higher in DXA measurements of bi‐iliac breadth and medio‐lateral pelvic inlet breadth and higher for MRI measurements of bi‐acetabular breadth. Bland Altman analyses showed no statistically significant relationship between the mean bias of MRI and DXA, and the differences between MRI and DXA pelvic measurements. Conclusions: DXA measurements of pelvic breadth are comparable to MRI measurements of pelvic breadth. DXA is a less costly imaging technique than MRI and can be used to collect measurements of skeletal elements in living people.